Mycorrhizal fungal community structure in tropical humid soils under fallow and cropping conditions. Issue 1 (December 2018) - Jemo, Martin; Dhiba, Driss; Hashem, Abeer; Abd_Allah, Elsayed; Alqarawi, Abdulaziz; Tran, Lam-Son
Abstract Little is known to what extent soil biota, in particular, the mycorrhizae are altered through different fallow durations/types in tropical soils. We found that soil-N, -C, -Al, -K and -Ca contents significantly differed due to the fallow durations/types. Subsequently, the effects of fallow types and soil depths on the diversity, species richness and community structure of arbuscular mycorrhizal (AM) fungi were examined. A higher AM species richness was identified in the cropping than in forest fallow fields, suggesting a positive cropping feedback on the AM community composition. Distribution of the AM species was positively related to soil properties, specifically soil-pH, and soil-Pi, -Ca and -Mg contents. The soil properties conjointly accounted for 78.5% of explained variation in the AM community composition, signifying that the main factors altering the community structure under different fallow and cropping systems were the soil properties. Among the soil chemical characteristics, the soil-pH disclosed a significant explained variation in the AM community composition in the topsoil layer under the short fallow. Structural modeling equation to understand multiple predictive pathways that connect soil properties, fallow practices and AM community structures indicated that soil-C, -N and -Ca contents were highlighted as important factors influencing the AM community compositions.